O trabalho do assistente social no contexto hospitalar: uma análise na perspectiva do trabalho em equipe - Mello, Cristiane Ferraz Quevedo de (2012)
This thesis constitutes a qualitative study about the work involved in the social worker in the hospital, and is anchored in research that is based on the theory and historical-dialectical materialist method. The problem part of the following research question: "how the social workers to the hospital system develop its work in teams where they live?" In order to analyze the work of the social worker of the hospital network, from the perspective of teamwork in order to qualify the integral and humanized care to the user. The research subjects were nine (09) professionals who work in health teams in hospitals, in Porto Alegre, including: social workers, doctors, nurse, psychologist and speech therapist. In the process of data collection, we used a semi-structured interview technique with application form consisting of open questions. The data collected were subjected to content analysis of crop-based thematic Bardin (1977), identifying thematic topics and frequency of communications professionals, according to summaries of the themes or explanatory of reality: the social worker the health teams, team work, comprehensiveness and humanization that support for the discussion and propositions woven.